THE EFFECTIVENESS OF ZIS FUNDS MANAGEMENT IN THE FIELD OF EDUCATION IN LAZISMU SURABAYA CITY - Nurulita Ipmawati; Tika Widiastuti (Universitas Airlangga, 2020)
This study aims to determine the effectiveness of ZIS funds in the field of education at LAZISMU Surabaya City. The research method used in this study was descriptive qualitative with a research strategy using case studies. Data collection carried out in this study is by observation, interviews, and documentation. Data analysis techniques were by reducing data, presenting data, and drawing conclusions. The results of this study indicate that ZIS funds managed by LAZISMU are effective, including input standards, process standards and output standards. To help the educational sector, LAZISMU needs to increase educational scholarship funds.Keywords: effectiveness, education fund, ZIS, LAZISMUREFFERENCE Azis, H. A., Widiastuti, T., Mawardi, I., Herianingrum, S., HR, M. N., Ratnasari, R. T., Murniati, R. (2017). Zakat & pemberdayaan. Surabaya: Airlangga University Press.Badan Amil Zakat Nasional. (2011). Penerimaan dan penyaluran tahun 2011. Diambil dari www.baznas.or.idDavid Krech, Richard S . Cruthfield dan Egerton L. Ballachey. (1982). Individual and society. New York: McGraw-Hil.Danim Sudarwan. (2012). Motivasi kepemimpinan dan efektivitas kelompok. Jakarta: PT. Rineka Cipta.Gunawan, Ary H. (2000). Sosiologi pendidikan suatu analisis sosiologi tentang berbagai problem pendidikan. Jakarta: PT. Rineka Cipta.Mahmudi, (2005). Manajemen kinerja sektor publik. Yogyakarta: UPP AMP YKPN.Sugiyono. (2012). Metode penelitian kuantitatif, kualitatif, dan R&D. Bandung: Alfabeta.